Hubungan Tingkat Pendidikan dan Pengetahuan Ibu Dengan Kejadian Stunting Pada Balita Usia 24-59 Bulan Di Wilayah Kerja Puskesmas Monggeudong Kota Lhokseumawe - Berlina, Liza; Sawitri, Harvina; Mauliza, Mauliza (FAKULTAS ILMU KESEHATAN UNIVERSITAS MUHAMMADIYAH PAREPARE, 2024)
Stunting is a nutritional problem in the world, especially in poor and developing countries, stunting is a major health problem associated with the risk of morbidity and mortality, sub-optimal brain development, resulting in delayed motor changes and stunted mental growth. The purpose of this study was to determine the relationship between mother's level of education and knowledge with the incidence of stunting in toddlers aged 24-59 months in the working area of the Mongeudong Public Health Center, Lhokseumawe City. This type of research is an observational analytic study with a cross-sectional design. The total population in this study was 888 people. The sample was taken using a non-probability sampling technique with accidental sampling and obtained a sample of 80 respondents. Data analysis in this study was univariate and bivariate analysis using the chi-square test statistical test. The results of the statistical test showed that the education level variable (p = 0.000 <, a = 0.05) and the knowledge variable (p = 0.000 <, a = 0.05). The conclusion of this study is that there is a relationship between the mother's level of education and knowledge with the incidence of stunting in toddlers aged 24-59 months in the working area of the Mongeudong Public Health Center, Lhokseumawe City.